2018
DOI: 10.1038/s41598-018-36407-y
|View full text |Cite
|
Sign up to set email alerts
|

Publisher Correction: Early detection of pulmonary exacerbations in children with Cystic Fibrosis by electronic home monitoring of symptoms and lung function

Abstract: A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has been fixed in the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Several investigators have reported the use of telehealth or HM in people with CF, but the vast majority have been small feasibility studies with limited external validity. 615 Lechtzin et al 17 recently reported the results of the eICE study, the first large multicentre randomised controlled study of HM in CF. The primary outcome (absolute change in FEV1 over the 52-week study period) was negative, with no evidence of slowing lung function decline over the 12-month study period in the HM group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigators have reported the use of telehealth or HM in people with CF, but the vast majority have been small feasibility studies with limited external validity. 615 Lechtzin et al 17 recently reported the results of the eICE study, the first large multicentre randomised controlled study of HM in CF. The primary outcome (absolute change in FEV1 over the 52-week study period) was negative, with no evidence of slowing lung function decline over the 12-month study period in the HM group.…”
Section: Discussionmentioning
confidence: 99%
“…Since symptoms often gradually deteriorate during a PEx, 5 there has been interest in using home monitoring (HM) to start treatment more promptly and to potentially improve the outcomes of people with CF. 617…”
Section: Introductionmentioning
confidence: 99%
“…In fact, several retrospective studies have shown an increase in pulmonary exacerbation or decline in lung function among patients with CF on chronic PPI therapy. [59][60][61] A prior in vitro study demonstrated that primary bronchial epithelial cells stimulated by gastric juice from patients on PPI therapy induced higher IL-8 production than those from patients off PPI. 62 For surgical antireflux therapy, prior retrospective studies, which have largely been limited to case series comparing pre and postsurgical clinical course, have shown a decrease in pulmonary exacerbation rate and an improvement in lung function on PFT after antireflux surgery.…”
Section: Cystic Fibrosis and Gerdmentioning
confidence: 99%
“…However, a definite protective role by medical acid suppression therapy against pulmonary complications of CF has not been demonstrated. In fact, several retrospective studies have shown an increase in pulmonary exacerbation or decline in lung function among patients with CF on chronic PPI therapy 59–61 . A prior in vitro study demonstrated that primary bronchial epithelial cells stimulated by gastric juice from patients on PPI therapy induced higher IL‐8 production than those from patients off PPI 62 .…”
Section: Cystic Fibrosis and Gerdmentioning
confidence: 99%